The Structure of Mangrove Community in The Waters of Pare Mas Jerowaru East Lombok - Nindi Hamida Lutfiani; Agil Al Idrus; Didik Santoso (Jurnal Biologi Tropis, 2023)
Mangrove communities grow well in the tropics and are able to adapt to extreme environments, such as: high temperature, high salinity, extreme tides, high sedimentation, and oxygen-poor growing substrate conditions. Information about mangrove ecology is very important to provide an overview of the current condition of mangroves. The aim of this research is to determine the structure of the mangrove community in Pare Mas Jerowaru, East Lombok. This research used a purposive sampling method and a combination of line and quadrat transects. The research results obtained 3 types of mangroves in Pare Mas waters. The diversity index value is in the low category and the dominance index value is medium to high. The species Rhizophora apiculata had the highest frequency value (0.57 ind/m²) and the lowest was Avicennia marina (0.10 ind/m²). Density at the tree level is in the sparse category, while at the pole, sapling and seedling level it is in the medium to very dense category. The types of mangroves that have the highest cover values in the tree, pole and stake categories are Sonneratia alba and Rhizophora apiculata. The highest INP values in the categories of trees, poles, saplings and seedlings were 272.99% (Sonneratia alba), 173.58% (Sonneratia alba), 215.51% (Rhizophora apiculata) and 200.00% (Rhizophora apiculata).